A qualitative investigation of the impact of asthma and self-management strategies among older adults. (2nd January 2017) - O'Conor, Rachel; Martynenko, Melissa; Gagnon, Monica; Hauser, Diane; Young, Edwin; Lurio, Joseph; Wisnivesky, Juan P.; Wolf, Michael S.; Federman, Alex D.; ,
ABSTRACT: Objective: We sought feedback from elderly patients living with asthma to understand their experience with assuming self-management roles for their asthma in order to inform the design and implementation of a primary care-based strategy that could best support their asthma control. Methods: We held six focus groups with a total of 31 English- and Spanish-speaking older adults with a current diagnosis of asthma. Focus groups addressed the effect of asthma on patients' lives and self-management strategies. Transcripts were analyzed using constant comparative techniques. Results: Asthma exerted a consistent effect on patients' physical and psychological well-being. Common barriers to self-care included misuse of controller medications and uncertainty whether shortness of breath, fatigue, and cough were due to their asthma or some other chronic illness. Patients developed coping strategies to continue with daily activities even when experiencing symptoms, but did not recognize attainable asthma quality of life. Conclusions: Asthma had a distinct impact on elderly adults' quality of life; due to their longstanding history with this condition, many patients had accepted these symptoms as a "new normal." Developing strategies to reorient patients' perceptions of the possibilities for managing their illness will be critical to the success of asthma self-management support programs specific to older adults.